1992
DOI: 10.1021/ie00009a023
|View full text |Cite
|
Sign up to set email alerts
|

Optical diagnostic methods for the study of fuel fouling

Abstract: 2243the amount of the imbibed cornpitions and increased the intrinsic reactivity. However, the reactivity decreased abruptly in a high concentration of NaCl salts due to the limitation of the rate of ion exchange and the decrease of the degree of hydration of the active catalyst site.An experimental study of fuel fouling using optical measurement methods was performed. These measurements included absorption from 350 to 750 nm, scattering at 514.5 nm, and fluorescence using a probe wavelength of 514.5 nm. Measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Cheng et al used UV−vis absorption spectroscopy in accelerated oxidation tests to measure the amount of soluble gums. Parker et al studied the fouling phenomena of JP-4 fuel using a combination of optical measurements: light absorption spectra from 350 to 750 nm, elastic light scattering at 514.5 nm for particle size measurements, and monochromatic fluorescence collected in the visible spectrum. The authors concluded that all three techniques showed an ability to monitor changes within the thermally stressed fuel.…”
Section: Review Of Optical Diagnostics and Fuel Thermal Stabilitymentioning
confidence: 99%
“…Cheng et al used UV−vis absorption spectroscopy in accelerated oxidation tests to measure the amount of soluble gums. Parker et al studied the fouling phenomena of JP-4 fuel using a combination of optical measurements: light absorption spectra from 350 to 750 nm, elastic light scattering at 514.5 nm for particle size measurements, and monochromatic fluorescence collected in the visible spectrum. The authors concluded that all three techniques showed an ability to monitor changes within the thermally stressed fuel.…”
Section: Review Of Optical Diagnostics and Fuel Thermal Stabilitymentioning
confidence: 99%
“…[10][11] Much of this work also developed new infra-red emission and absorption techniques for probing dense particulate-and droplet-laden flowfields associated with diesel spray injection and hightemperature fuel fouling. [12][13][14] In the early 90's, PSI conducted numerous research programs in support of major national projects to develop high-speed propulsion systems for hypersonic flight vehicles. Our reaction kinetics expertise was deployed to measure three-body recombination rates important in designing efficient SCRAMJET engines 15 and to interpret experimental H 2 -air combustion data obtained in a PSI shock tunnel supersonic combustion facility (shown in Figure 2).…”
Section: Reaction Kineticsmentioning
confidence: 99%